2008
DOI: 10.1590/s0103-84782009005000068
|View full text |Cite
|
Sign up to set email alerts
|

Porta-enxertos para a tangerineira 'Michal' no Rio Grande do Sul

Abstract: IIIPorta-enxertos para a tangerineira 'Michal' no Rio Grande do Sul

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…However, Yonemoto et al (2004) observed that 'Shirakawa' satsuma grafted on 'Flying Dragon' had higher soluble solids in comparison to those on P. trifoliata, independently of the fruit load on trees. Rootstocks had no effect on JC, as reported by other authors (Koller et al, 2000;Pérez-Zamora et al, 2002;Castle et al, 2007;Espinoza-Núñez et al, 2007;Mourão Filho et al, 2007;Brugnara et al, 2009).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…However, Yonemoto et al (2004) observed that 'Shirakawa' satsuma grafted on 'Flying Dragon' had higher soluble solids in comparison to those on P. trifoliata, independently of the fruit load on trees. Rootstocks had no effect on JC, as reported by other authors (Koller et al, 2000;Pérez-Zamora et al, 2002;Castle et al, 2007;Espinoza-Núñez et al, 2007;Mourão Filho et al, 2007;Brugnara et al, 2009).…”
Section: Resultssupporting
confidence: 74%
“…These plants showed similar vegetative characteristics to eight-year-old 'Monte Parnaso' orange (Reis et al, 2008) and ten-year-old 'Michal' mandarin (Brugnara et al, 2009) trees in the same orchard. Canopy height and volume reduction of plants budded onto 'Flying Dragon', in comparison to 'Troyer', are similar to the reduction observed by Roose (1986) for 'Valencia' orange.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The juice yield was higher than 35% in all seasons (Figure 4 B); this value is considered suitable for marketing of orange fruit in the state of São Paulo (GRIZOTTO et al, 2012;BRUGNARA et al, 2009;CEAGESP, 2000). The high percentage of juice is a very interesting characteristic for citrus cultivars, both for those that will be used for fresh consumption and those used for processing (BARBASSO et al, 2005).…”
Section: Fruit Mass and Juice Yieldmentioning
confidence: 86%
“…Other studies comparing these rootstocks in citrus cultivars, such as 'Montenegrina' tangerine (Toniolli et al, 1993), have also found 'Swingle' citrumelo to have the most developed plants. Brugnara et al (2009) also reported that the trifoliate provides less volume in the canopy 'Michal' tangerine in Rio Grande do Sul than more vigorous rootstocks such as 'Rangpur' lime or 'Swingle' citrumelo.…”
Section: Vegetative Growth and Productivitymentioning
confidence: 98%